2022
DOI: 10.1128/spectrum.01334-21
|View full text |Cite
|
Sign up to set email alerts
|

Species-Wide Phylogenomics of the Staphylococcus aureus Agr Operon Revealed Convergent Evolution of Frameshift Mutations

Abstract: Staphylococcus aureus is a globally pervasive pathogen that produces a plethora of toxic molecules that can harm host immune cells. Production of these toxins is mainly controlled by an active agr quorum-sensing system, which senses and responds to bacterial cell density.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 86 publications
3
32
0
Order By: Relevance
“…Sequences were grouped into clonal complexes using the eBURST algorithm [31]. The agr type was assigned using AgrVATE (v1.0.2) [32] and spa type using spaTyper (v0.3.1) [33]. Average nucleotide identities (ANI) were calculated using fastANI [34].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were grouped into clonal complexes using the eBURST algorithm [31]. The agr type was assigned using AgrVATE (v1.0.2) [32] and spa type using spaTyper (v0.3.1) [33]. Average nucleotide identities (ANI) were calculated using fastANI [34].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were grouped into clonal complexes using the eBURST algorithm (30). The agr type was assigned using AgrVATE (v1.0.2) (31) and spa type using spaTyper (v0.3.1) (32). Average nucleotide identities (ANI) were calculated using fastANI (33).…”
Section: Methodsmentioning
confidence: 99%
“…2c), is an agonist of both AgrC4 and AgrC1 but an inhibitor of AgrC2 and AgrC3 [28,29]. Recently Raghuram et al [32] developed a software tool (AgrVATE; github.com/VishnuRaghuram94/AgrVATE) to interrogate S. aureus agr variability and evolution. Analysis of ~40 000 S. aureus genomes revealed that the distribution of the four agr groups is ~60 % group I, ~22 % group II, ~14 % group III and ~2.5 % group IV [32].…”
Section: The S Aureus Agr Systemmentioning
confidence: 99%
“…Recently Raghuram et al [32] developed a software tool (AgrVATE; github.com/VishnuRaghuram94/AgrVATE) to interrogate S. aureus agr variability and evolution. Analysis of ~40 000 S. aureus genomes revealed that the distribution of the four agr groups is ~60 % group I, ~22 % group II, ~14 % group III and ~2.5 % group IV [32]. This extensive in silico analysis did not uncover any novel agr groups, intermediate AIPs or AIPs acquired from CONS.…”
Section: The S Aureus Agr Systemmentioning
confidence: 99%
See 1 more Smart Citation